Enter literal equation

Enter variable to solve for:


Given the literal equation 2(x+a)=4b

Solve this for x

Simplify by removing parentheses
Simplify 2(x + a):
Distribute the 2 to each term in (x+a)
2 * x = (2 * 1)x = 2x
2 * a = (2 * 1)a = 2a
Our Total expanded term is 2x + 2a

Our new term is
2x + 2a = 4b

Solve the following literal equation for x

2x + 2a = 4b

Isolate x terms

Add - 2a to both sides

2x + 2a - 2a = 4b - 2a

2x = 4b - 2a

Divide each side by 2

2x
2
=
  
4b - 2a
2

x  =  4b - 2a
  2